Urban forest protection from the perspective of environmental law in Malaysia: issues and challenges - Mustafa, Maizatun (RICS, 2009)
Within a society, ongoing urbanisation can lead to the increasing importance of urban green spaces as contributors to the quality of the urban environment and urban life globally. Forest and tree resources are known to have a wide range of socio-cultural, economic and environmental values. The value of the forest is also increasingly recognised as extending beyond rural areas and so trees must become compatible with and functional in the urban environment. At present, the emerging realization of the importance of these values has become apparent to many countries, including that of Malaysia. Upon this realization, Malaysia began to consider ways to optimize and incorporate forest values within its urban environs in a sustainable way while responding to the wide range of needs, local priorities and expectations. This paper examines the scope of urban forest and the role of urban greening in enhancing the living quality of urban populations of Malaysia. The paper is deliberately biased towards environmental issues and aims at highlighting provisions under environmental law relevant to urban forest protection. Some issues pertaining to possible challenges that can undermine the efficacy of the law are also highlighted.